Investigation on the potential use of thorium as fuel for the Sodium-cooled Fast Reactor. (May 2017) - György, H.; Czifrus, Sz.
Highlights: Investigation of the European concept of SFR for base parameters. Burnup calculation of a pre-concept Th containing core for initial amount of 233 U. Study of two SFR core concepts (TSFR-FC and TSFR-IC). Examination of possible final versions of the concepts. Study of 233 U production, operational and safety parameters. Abstract: Generation IV reactors are planned to be an evolutionary step in the history of nuclear power plants. Although they have many advantageous properties, five of the six concepts are designed for the utilization of uranium–plutonium fuel. In this paper, the Sodium-cooled Fast Reactor is investigated regarding the potential application of thorium. The basis of the investigation is the European concept of SFR, which is studied with thorium-containing fuel compositions. Two different approaches are presented with the results of several full-core burnup calculations performed by the Monte Carlo code Serpent 2. The presented results are the multiplication factor changes, delayed neutron fractions, fuel temperature and void coefficients and fissile isotope vectors as well. The results can help to determine how 233 U could be produced in this type of reactors and how it could be used as alternative fuel in SFR.